2007
DOI: 10.3852/mycologia.99.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Association of ergot alkaloids with conidiation in Aspergillus fumigatus

Abstract: Ergot alkaloids are mycotoxins that affect the nervous and reproductive systems of exposed individuals through interactions with monoamine receptors. They have been studied more widely in ergot fungi and grass endophytes but also are found in Aspergillus fumigatus, an opportunistic human pathogen that reproduces and disseminates exclusively through conidia. The ergot alkaloids festuclavine and fumigaclavines A, B and C are present in or on conidia of A. fumigatus. Cultures of the fungus that are free of conidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
(1 reference statement)
1
23
0
1
Order By: Relevance
“…In A. fumigatus, ergot alkaloids are produced in the asexual reproductive structures known as conidia and not in vegetative structures (Coyle, Kenaley, Rittenour, & Panaccione, 2007). Since the average mass of a conidium is 2.9 pg , the mass of conidia in an extract can be calculated by counting spore dilutions on a hemocytometer.…”
Section: Extraction Of Ergot Alkaloids From Mold Culturesmentioning
confidence: 99%
“…In A. fumigatus, ergot alkaloids are produced in the asexual reproductive structures known as conidia and not in vegetative structures (Coyle, Kenaley, Rittenour, & Panaccione, 2007). Since the average mass of a conidium is 2.9 pg , the mass of conidia in an extract can be calculated by counting spore dilutions on a hemocytometer.…”
Section: Extraction Of Ergot Alkaloids From Mold Culturesmentioning
confidence: 99%
“…With a few exceptions, localization of these steps in the fungal thallus -whether tissue specificity or cellular localization -is largely unknown. A few studies have shown that certain secondary metabolites localize to specific tissues, such as endocrocin and fumigaclavines to asexual spores (conidia) of the human opportunistic pathogen Aspergillus fumigatus (Coyle et al, 2007;Berthier et al, 2013). The mechanism(s) resulting in placement of metabolites into spores is not known although the study on fumigaclavine synthesis suggests a need for BrlA, the Aspergillus transcription factor required for asexual sporulation (Coyle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ergot alkaloid synthesis genes are clustered in the A. fumigatus genome [10,11] and are expressed during asexual reproduction [13,14]. Aspergillus nidulans , a model fungus that is closely related to A .…”
Section: Introductionmentioning
confidence: 99%